2017
DOI: 10.1530/joe-17-0131
|View full text |Cite
|
Sign up to set email alerts
|

The interaction of MC3R and MC4R with MRAP2, ACTH, α-MSH and AgRP in chickens

Abstract: The interaction of melanocortin-4 (MC4R) and melanocortin-3 (MC3R) receptors with proopiomelanocortin (POMC)-derived peptides (e.g. α-MSH), agouti-related protein (AgRP) and melanocortin-2 receptor accessory protein 2 (MRAP2) is suggested to play critical roles in energy balance of vertebrates. However, evidence on their interaction in birds remains scarce. Our study aims to reveal their interaction in chickens and the results showed that (1) chicken (c-)MC3R and cMC4R expressed in Chinese hamster ovary (CHO) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

25
93
2
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 53 publications
(121 citation statements)
references
References 84 publications
25
93
2
1
Order By: Relevance
“…Fridmanis ' s study reported that ACTH stimulation increases the expression of MC2R, but this phenomenon has always been considered to occur via ACTH activation of the cell membrane surface MC2R, which activates MC2R production through a series of signal pathways to increase its own expression level . Many studies have shown that the lack of MRAP‐trapped MC2R becomes the endoplasmic reticulum and impairs membrane localization, which may participate in the activation process of MC2R . In our study, MRAP expression was observed in VSMCs, as was an increase in MRAP dimerization and glycosylation levels after ACTH stimulation, but no localization changes in MRAP and MC2R were observed.…”
Section: Discussionsupporting
confidence: 46%
See 2 more Smart Citations
“…Fridmanis ' s study reported that ACTH stimulation increases the expression of MC2R, but this phenomenon has always been considered to occur via ACTH activation of the cell membrane surface MC2R, which activates MC2R production through a series of signal pathways to increase its own expression level . Many studies have shown that the lack of MRAP‐trapped MC2R becomes the endoplasmic reticulum and impairs membrane localization, which may participate in the activation process of MC2R . In our study, MRAP expression was observed in VSMCs, as was an increase in MRAP dimerization and glycosylation levels after ACTH stimulation, but no localization changes in MRAP and MC2R were observed.…”
Section: Discussionsupporting
confidence: 46%
“…25 Many studies have shown that the lack of MRAP-trapped MC2R becomes the endoplasmic reticulum and impairs membrane localization, which may participate in the activation process of MC2R. 24 In our study, MRAP expression was observed in VSMCs, as was an increase in MRAP dimerization and glycosylation levels after ACTH stimulation, but no localization changes in MRAP and MC2R were observed. The above questions require further study.…”
Section: Figuresupporting
confidence: 44%
See 1 more Smart Citation
“…In chickens, MC3R and MC4R can be activated by α-MSH or ACTH. But AgRP can antagonize α-MSH or ACTH actions on MC3R/MC4R and lower the constitutive activity of MC3R and MC4R (Zhang et al 2017). In mice, knockout of MC5R exhibit a severe dysfunction of exocrine secretion (Chen et al 1997).…”
Section: Introductionmentioning
confidence: 99%
“…MRAP2b can decrease the constitutive activity of MC4R during fasting which suggests that the deletion of MRAP2b may induce growth changes or obesity. As in zebrafish, MRAP2 can enhance the sensitivity of MC4R for ACTH and block the constitutive activity of MC4R in chickens (Zhang et al 2017). Unlike MC4R, the physiological functions between MC5Rs and MRAP2 proteins are largely unknown in zebrafish.…”
Section: Introductionmentioning
confidence: 99%